Predisposing Risk Factors Affecting Reversibility of Left Ventricular Diastolic Filling Pattern in Patients with Preserved Ejection Fraction - Kim, Dong-Gil; Cho, Sungsoo; Park, Seongjin; Kim, Gi Rim; Ko, Kyu-Yong; Kim, Sung Eun; Hwang, Ji-won; Doh, Joon-Hyung; Kwon, Sung Uk; Kwak, Jae-Jin; Namgung, June; Cho, Sung Woo (Yonsei medical journal, 2025)
Improvement of left ventricular (LV) diastolic dysfunction (DD) is known to be a good prognostic factor in patients with heart failure with reduced ejection fraction (EF). In the present study, we investigated the predisposing risk factors affecting the reversibility of LV diastolic filling pattern (DFP) in patients with preserved EF. A total of 600 patients with pseudonormal LVDFP and preserved EF who underwent follow-up echocardiography were enrolled between 2011 and 2020. We compared their index and follow-up echocardiography findings and determined the predisposing risk factor affecting the reversibility of LVDFP. Comparing the index and follow-up echocardiography findings showed that 379 (63%) patients had improved to normal or impaired relaxation LVDFP (improved group) and 221 (37%) patients had maintained or worsened LVDFP (unimproved group). The incidence of paroxysmal atrial fibrillation (PAF) was significantly higher in the unimproved group than in the improved group (4.7% vs. 9.5%, =0.026). After adjustment for relevant clinical risk factors of diastolic dysfunction, PAF was determined to be an independent predisposing risk factor for the unimproved LVDFP (odds ratio: 2.10, 95% confidence interval: 1.06-4.15, =0.033). Among the parameters of diastolic dysfunction in follow-up echocardiography, the left atrial volume index, mean E/A ratio, and E/e' were significantly improved in patients without PAF but remained in patients with PAF. We identified that PAF was an independent predisposing risk factor of the unimproved LVDFP in patients with pseudonormal LVDFP and preserved EF. Therefore, early detection and management of PAF might be required in patients with LVDD and preserved EF to prevent adverse cardiovascular events.